2017
DOI: 10.1159/000481691
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Lipid Nanoparticles Containing Natural Botanical Oil for Sun Protection: Characterization and in vitro and in vivo Human Skin Permeation and Toxicity

Abstract: The use of sunscreen products is widely promoted by schools, government agencies, and health-related organizations to minimize sunburn and skin damage. In this study, we developed stable solid lipid nanoparticles (SLNs) containing the chemical UV filter octyl methoxycinnamate (OMC). In parallel, we produced similar stable SLNs in which 20% of the OMC content was replaced by the botanical urucum oil. When these SLNs were applied to the skin of human volunteers, no changes in fluorescence lifetimes or redox rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Cosmetic O/W creams containing basil essential oil (5% (w/w)) have been proposed as potential sunscreen formulations for cosmetic and cosmeceutical uses [5]. Andréo-Filho et al [6] investigated the photoprotective effect of solid lipid nanoparticles loaded with an organic sunscreen agent (octyl methoxycinnamate) and urucum oil, and concluded that the use of vegetable oils could allow sunscreen formulations to contain reduced amounts of organic UV-filters while maintaining the same SPF.…”
Section: Of 10mentioning
confidence: 99%
See 1 more Smart Citation
“…Cosmetic O/W creams containing basil essential oil (5% (w/w)) have been proposed as potential sunscreen formulations for cosmetic and cosmeceutical uses [5]. Andréo-Filho et al [6] investigated the photoprotective effect of solid lipid nanoparticles loaded with an organic sunscreen agent (octyl methoxycinnamate) and urucum oil, and concluded that the use of vegetable oils could allow sunscreen formulations to contain reduced amounts of organic UV-filters while maintaining the same SPF.…”
Section: Of 10mentioning
confidence: 99%
“…Therefore, a significant amount of attention has been focused on vegetable oils, owing to their many biological activities and attractive technological properties, such as easy skin absorption and good spreadability [1][2][3]. Recently, selected herbal oils have been investigated to develop sunscreen formulations with a reduced content of organic UV-filters while still maintaining a high sun protection factor (SPF) [4][5][6]. Indeed, the safety of organic UV-filters has been widely debated because some studies on the skin penetration and permeation of these molecules have reported that they are able to permeate the skin at sufficient rates to be recovered from systemic circulation [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Such naturally occurring sunscreen agents that can combine both pigment and antioxidant properties may come from plant extracts such as green tea polyphenols, silymarin from milk thistle, proanthocyanidins from grape seeds, etc. [ 37 , 38 ]. Annatto, which comes from the family of Bixaceae (Achiote family), grows to a height of 2–5 m and is well distributed in Karnataka, Andhra Pradesh, Assam, Tamil Nadu, and Orissa (India).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological studies have been revealed that saffron extracts or its constituents have antitumor, hypolipidemic, radical scavenging, antinociceptive, anti-inflammatory, anticonvulsant, antidepressant, and antioxidant properties [ 41 , 42 , 43 , 44 , 45 ]. Therefore, due to the combination of pigment and antioxidant properties, several attempts have been made in order to prepare sunscreen formulations based on annatto or saffron [ 38 , 39 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Andréo-Filho et al have loaded the OMC in solid colloidal nanocarriers composed of a lipid base and vegetable oils. They also developed another formula with the replacement of 20% of OMC amount with urucum oil to decrease the used amount of chemical UV filter and could reduce the oxidative stress or radiation-induced inflammation ( Andreo-Filho et al, 2018 ). The designed two formulas didn't demonstrate any toxic effect on the skin.…”
Section: Applications Of Lnps In Cosmeceuticalsmentioning
confidence: 99%